2018
DOI: 10.5812/asjsm.61013
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ten-Week FIFA 11+ Injury Prevention Program for Kids on Performance and Fitness of Adolescent Soccer Players

Abstract: Background: Soccer is the world's most popular sport, with most players being younger than 18 years. "FIFA 11+ Kids" has been recently introduced to prevent soccer injuries in adolescent players. This program would be more accepted and followed by coaches and players if it were to also promote performance and physical fitness in players. The purpose of this study was to assess the effect of a ten-week FIFA 11+ for kids Injury prevention program on performance and physical fitness in adolescent soccer players.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(44 citation statements)
references
References 29 publications
0
40
1
3
Order By: Relevance
“…In this respect, it can be stated that since the third part of the 11+ training involves running training with diversion (crop motions) (19), the agility time improvement was seen in these studies. However, contrary to the findings of the present study, Zarei et al (18) reported that the FIFA 11+ program for children did not affect vertical jump performance and agility of adolescent soccer players. Moreover, Impellizzeri et al (19) suggested that the 11+ training, despite its effect on knee flexing muscle strength, did not have a real impact on the agility and vertical jump of soccer players.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In this respect, it can be stated that since the third part of the 11+ training involves running training with diversion (crop motions) (19), the agility time improvement was seen in these studies. However, contrary to the findings of the present study, Zarei et al (18) reported that the FIFA 11+ program for children did not affect vertical jump performance and agility of adolescent soccer players. Moreover, Impellizzeri et al (19) suggested that the 11+ training, despite its effect on knee flexing muscle strength, did not have a real impact on the agility and vertical jump of soccer players.…”
Section: Discussioncontrasting
confidence: 99%
“…However, contrary to the above results, some studies indicated the ineffectiveness of FIFA 11+ injury prevention program in promoting athletes' performance. For example, in Zarei et al study (18), a 10-week FIFA 11+ injury prevention program had no significant effect on the improvement of zigzag dribbling, Illinois, sitting and reaching, vertical jump, 20 m sprint, and Planck sideways. Also, nine weeks of FIFA 11+ training had no significant effect on improving balance, speed, agility, and vertical jump (19).…”
Section: Introductionmentioning
confidence: 96%
“…One of the most important reasons can be considered the lack of a similarity in some stages of the 11+kids and 11+ exercises. 11+ Kids exercises mainly focus on improving coordination, balance, landing technique, strengthening the leg muscles and core stability muscles and may be more appropriate than 11+exercises for the pre-adolescents (36).Two and three balance exercises, especially on one leg and jump exercises (Exercises 1, 2 and 3) might be reasons for the success of 11+ Kids exercises in enhancing the dynamic balance and jump tests in the pre-adolescent players (36). The balance exercises increase the neural adaptation and inhibitory stimulation of spinal reflexes, such as stretching reflexes, and increase the co-contraction pattern in the agonist and antagonist muscles, ultimately leading to improved balance (43).…”
Section: Discussionmentioning
confidence: 99%
“…Injury incidence among soccer players differs across levels of participation, age, type of exposure, and sex [ 1 , 8 , 15 , 16 , 17 ] with soccer players under the age of 12 years exhibiting a lower injury rate (1.0–1.6 injuries per 1000 h) compared to older players [ 1 , 16 , 17 ]. However, this rate varies considerably among different studies.…”
Section: Introductionmentioning
confidence: 99%
“…Only a few studies were aimed at identifying risk factors for injuries in youth soccer, such as neuromuscular imbalances, fatigue, biomechanical factors, and previous injuries [ 15 , 21 , 23 , 24 ]. However, in addition to these, other factors which may increase the potential for injury in sport should be analyzed.…”
Section: Introductionmentioning
confidence: 99%